Avaliação da aplicação de CO2 supercrítico na presença de cosolventes para a reciclagem de placas de circuito impresso de celulares - Calgaro, Camila Ottonelli (2015)
Technological development and intensive marketing support the growth of demand for electrical and electronic equipment (EEE), which have as a primary component printed circuit boards (PCBs). These devices have become obsolete in a shorter period of time, then residual PCBs become a problem, requiring recycling. The PCBs are composed of ceramic, polymers and metals, especially copper, metal present in the highest percentage. In addition they contain toxic substances such as brominated flame retardants and heavy metals. So the PCBs represent a problem and an opportunity at the same time, they require proper treatment and they are composed for materials with economic value. Therefore the aim of this study was to evaluate the application of supercritical CO2 and co-solvents in the recovery of copper and polymers from mobile phone PCBs, for the development of a more efficient and environmentally friendly recycling process. The study involved the mechanical processing of PCBs separated from discarded mobile phones; the characterization of PCBs; copper recovery using the CO2 supercritical leaching and H2O2 and H2SO4 as cosolvents, this method was conducted comparatively with leaching at atmospheric pressure using H2O2 and H2SO4 as leaching agents; Electrowinning of copper supercritical leached; and recovering the polymer fraction contained in the PCBs, using ethanol as cosolvent. The results indicated that mechanical processing in two milling, carried out in a hammer mill and knives mill were important for the reduction of PCBs to particle diameter less than 2 mm. From the leaching with aqua regia, it was determined that the PCBs containing 34.83 wt% copper. The characterization steps have demonstrated that PCBs are composed of 64.02% of metal, 20.51% of ceramics and 15.47% of polymers. The results showed that the supercritical leaching is 9 times faster than the atmospheric leaching. About 90% of copper was extracted from PCBs in 20 min of supercritical leaching, employing a solid:liquid ratio of 1:20, 20% (v/v) H2O2 and H2SO4 (2.5M). From the electrowinning, performed in a current density of 250 A / m², the copper metal form was recovered with 95.97% purity, reaching a current efficiency of 99%. It was extracted 69.53% of the polymers present in the PCBs using supercritical CO2 and ethanol co-solvent at 170 ° C and 7.5 MPa. Therefore the application of supercritical CO2 and co-solvents is a promising method and efficient to PCBs recycling.